Teaching Listening Skill by Using Video (Audio-Visual) to the Eleventh Grade Students at SMA Al-Ikhlas Lubuklinggau - Aminah Khoiriyah; Maria Ramasari; Syaprizal Syaprizal (Journal of English Education, Literature and Linguistics, 2023)
This objective of the research was to prove whether there is significantly effective or not to use video in teaching listening for the eleventh grade students at SMA Al-Ikhlas Lubuklinggau. In this research, the researcher used pre-experimental method with one group pre-test and post-test. In collecting data, the researcher used the written test that was given twice to the students, pre-test and post-test. The researcher analyzed the data through individual score, normality testing, and matched t-test formula. The results showed that were 6 students passed the pre-test and 10 students failed in pre-test. While in the post-test, the students’ score increased, there were 14 students mastered the post-test and 2 students failed the post-test. In pre-test mean score was 66.25 and mean score in post-test was 85.31. The result of matched t-test, tobtained was 7.94 and ttable was 1.7531. it meant that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. So it was significantly effective to teach listening skill by using video media to the eleventh grade students at SMA Al-Ikhlas Lubuklinggau. Keywords: Listening Skill, Teaching, Video Media